FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI E-COMMERCE DAN DAMPAKNYA PADA KINERJA UMKM DI MASA PANDEMI COVID-19 (Studi Kasus Pelaku UMKM Di Kecamatan Singosari Kabupaten Malang) - Firda Rahayu Aisyah; Nur Diana (Universitas Islam Malang, 2022)
This study was conducted to analyze the factors that influence the adoption of e-commerce and its impact on the performance of UMKM during the Covid-19 pandemic. The research method used is quantitative research with a survey approach with a Likert 7-scale questionnaire data collection technique for UMKM located in Kecamatan Singosari, Kabupaten Malang. The sample calculation in this study uses the Maximum Likelihood guideline with 115 respondents. The analytical method in this study uses the Structural Equation Model (SEM) using AMOS 24.The results of the research hypothesis test show that environmental factors, technological factors, individual factors, and organizational factors have a simultaneous and significant effect on the adoption of e-commerce by UMKM. environmental, technological, organizational and individual factors have a positive and significant effect on e-commerce adoption in Kecamatan Singosari, Kabupaten Malang on e-commerce adoption in Kecamatan Singosari, Kabupaten Malang and e-commerce adoption has a positive and significant impact on UMKM performance. in Kecamatan Singosari, Kabupaten Malang.Keywords: e-commerce, environment, individual, technology, organizational, and UMKM performance, Pandemic Covid-19